Persistent myopathy despite release of partial obstruction: in vivo reversal of dysfunction and transcriptional responses using rapamycin. Issue 3 (27th January 2020) - Schröder, Annette; Aitken, Karen J.; Jiang, Jia‐Xin; Sidler, Martin; Tölg, Cornelia; Siebenaller, Aliza; Jeffrey, Nefateri; Kirwan, Tyler; Leslie, Bruno; Wu, Changhao; Weksberg, Rosanna; Delgado‐Olguin, Paul; et al.
Abstract: Current and potential medical therapy for obstruction‐induced myopathic bladder dysfunction (from benign prostatic hyperplasia or posterior urethral valves) focuses on symptoms. The persistent tissue pathology and dysfunction after release of obstruction is often deemed irreversible without any systematic therapeutic approaches. As rapamycin can attenuate bladder smooth muscle hypertrophy and dysfunction during the genesis of partial obstruction in vivo, we tested whether rapamycin could improve persistent function after release of obstruction (de‐obstruction or REL). Female Sprague‐Dawley rat bladders were partially obstructed (PBO) by suturing around both the urethra and a para‐urethral steel rod, then removing the rod. One day prior to release of obstruction (preREL), voiding parameters and residual urine volume of preREL+future rapa, preREL+future veh groups were recorded. Release of obstruction (REL) was performed by suture removal following 6 weeks of PBO. For 4 more weeks after the de‐obstruction, REL animals were randomized to rapamycin (REL+rapa) or vehicle (REL+veh). PBO for 6 weeks were used as positive controls. In shams, the urethra was exposed, but no suture tied. Voiding parameters and residual urine volume were measured prior to sacrifice of sham and REL+veh or REL+rapa, and PBO. Rapamycin efficacy was tested by pair‐wise comparison of changes in individual voiding data from preREL+future veh or preREL+future rapa versus REL+veh or REL+rapa, respectively, as well as by comparisons of REL+veh to REL+rapa groups. Bladders were weighed and processed for a high‐throughput QPCR array, and histopathology. Bladder/body mass ratios with PBO increased significantly and remained higher in the release phase in REL+veh animals. REL+rapa versus REL+veh improved residual volumes and micturition fractions toward sham levels. Three genes encoding extracellular proteins, BMP2, SOD3, and IGFBP7, correlated with functional improvement by Pearson's correlations. The promoters of these genes showed enrichment for several motifs including circadian E‐boxes. While obstruction and REL augmented CLOCK and NPAS2 expression above sham levels, rapamycin treatment during release significantly blocked their expression. This experimental design of pharmaco‐intervention during the de‐obstruction phase revealed a novel pathway dysregulated during the clinically relevant treatment phase of obstructive bladder myopathy.